A phenotypic comparison of proteoglycan production of intervertebral disc cells isolated from rats, rabbits, and bovine tails; which animal model is most suitable to study tissue engineering and biological repair of human disc disorders? - Miyazaki, T; Kobayashi, S; Takeno, K; Meir, A; Urban, J; Baba, H (Mary Ann Liebert Inc., 2009)
The nucleus pulposus (NP) of the intervertebral disc in cattle and humans shows the most dramatic changes with aging of any cartilaginous tissue. In humans, notochordal cells disappear from the NP and are replaced with chondrocytic cells by adolescence. However, notochordal cells of the NP persist into adult life in some species, such as rats and rabbits. Therefore, comparison of the metabolic activity of notochordal and nonnotochordal cells is considered to be important for determining the type of cell to use for transplantation to regenerate intervertebral discs. In this study, we investigated the notochordal NP cells of rats and rabbits, as well as nonnotochordal (chondrocyte-like) bovine NP cells, in a three-dimensional culture system to examine whether proteoglycan metabolism varied among these three cell types. As a result, bovine NP cells produced around 0.18 mg/mL of glycosaminoglycan after culture for 5 days, while rat and rabbit NP cells produced about four and two times more glycosaminoglycan than bovine cells, respectively. In conclusion, this study demonstrated marked differences of energy metabolism and production of matrix components between notochordal and nonnotochordal NP cells. Animals with notochordal cells in the NP, such as rats and rabbits, may not provide good models for investigation of biological repair and tissue engineering for human disc disorders.